TUTURAN EMOSI MAHASISWA KOTA BAUBAU DALAM RANAH DEMONSTRASI [Emotional Speech of The Students in Baubau City in The Demonstration] - risman iye (Kantor Bahasa Provinsi Maluku, 2018)
The variation of emotional utterances of the demonstrators rose the negative public attachments to the demonstration. This study aimed to explain: the form and type of emotional speech of Baubau City students in the realdemonstration. This research wa qualitative research. The Sampling were taken purposively. Oral data was collected by using the free-of-cognate method, documentation techniques, and notes. Data were analyzed with Searle's speech-actg theory and Goleman's theory. The result of the research showed that the form and type of emotional speech of Baubau city students in demonstration were four: words, phrases, sentences and idoms. Meanwhile, the types of emotional speech of Baubau City students in demonstration were anger, sadness, fearlessness, pleasure, and annoyance. Variasi tuturan emosi para demonstran memunculkan prasangka negatif masyarakat terhadap demonstrasi tersebut. Penelitian ini bertujuan untuk menjelaskan: bentuk dan jenis tuturan emosi mahasiswa Kota Baubau dalam ranah demonstrasi; Penelitian ini merupakan jenis penelitian kualitatif. Pengambilan sampel dilakukan secara purposif. Data lisan dikumpullkan menggunakan metode simak bebas cakap, teknik dokumentasi, dan catat. Data dianalisis dengan teori tindak tutur Searle dan teori Goleman. Hasil penelitian menunjukan bahwa bentuk tuturan emosi mahasiswa kota Baubau dalam ranah demonstrasi ada empat, yaitu kata, frasa, kalimat dan ungkapan Selanjutnya, jenis tuturan emosi mahasiswa Kota Baubau dalam ranah demonstrasi, yakni kemarahan, kesedihan, ketakutan, kenikmatan, dan kejengkelan.